Pengaruh Akses E-Commerce Terhadap Perilaku Konsumtif Remaja Dalam Perspektif Ekonomi Syariah - Pezi Rota Putra; Miti Yarmunida; Debby Arisandi (Journal of Innovative and Creativity, 2026)
Coffee Culture and Sense of Place: A Genius Loci Study of Warung Kopi Purnama in Bandung. This study aims to determine the effect of E-commerce access on adolescent consumer behavior from a sharia economic perspective in Bengkulu City. The research method used is quantitative with simple regression techniques and involved 100 respondents. The results of the study indicate that E-commerce access has a positive and significant effect on consumer behavior, evidenced by a regression coefficient value of 0.783 and a significance value of 0.000 <0.05. The R Square value of 0.648 indicates that E-commerce access contributes 64.8% to adolescent consumer behavior. This finding indicates that the higher the E-commerce access, the higher the tendency of adolescents to make impulsive purchases. From a sharia economic perspective, excessive consumer behavior is not in accordance with the principles of tawazun, qana'ah, as well as the prohibition of israf and tabdzir. Therefore, it is necessary to strengthen sharia economic literacy so that adolescents are able to behave in a wise manner in accordance with Islamic values. Keywords: E-commerce Access, Consumptive Behavior, Sharia Economy, Teenagers